Erasmus+ Programme in the Field of Higher Education: Cluster Analysis of European Countries - Oliinyk, Olena (Herald of Economics, 2026)
This article classifies European countries according to the level and structure of their participation in the Erasmus+ programme in the field of higher education based on a set of quantitative indicators from the 2024 call results, employing cluster analysis. The study employs methods of structural analysis, calculation of relative indicators, and hierarchical cluster analysis. The aggregation of quantitative indicators of Erasmus+ implementation across major education sectors in 2024 reveals a pronounced structural differentiation of the programme in terms of project scale, concentration of financial resources, and levels of institutional involvement. In 2024, a total of 27,761 projects were implemented within the programme, involving more than 62,000 organisations and a total funding volume of approximately EUR 3.69 billion. The results of the structural analysis indicate that higher education plays a system-forming role within the Erasmus+ programme: although it is not the largest sector in terms of the number of projects or participating organisations, it accumulates the majority of financial resources. The analysis of European countries’ participation in Erasmus+ in the field of higher education in 2024 demonstrates a high concentration of project activity. Out of a total of 5,830 higher education projects, almost half were implemented by only five countries: Spain, France, Germany, Italy, and Poland, which together accounted for more than 56% of total Erasmus+ grant funding allocated to higher education. The calculated relative participation intensity indicators confirm significant heterogeneity in countries’ involvement in the programme, while also revealing similar participation configurations among specific groups of countries. The dendrogram obtained from the hierarchical cluster analysis illustrates the grouping of European countries into four clusters based on the similarity of relative participation intensity configurations. The clustering results confirm the existence of several typical participation models that emerge independently of country size or level of economic development. Key clustering factors include the combination of funding intensity, average project scale, and the degree of institutional involvement.